Quelques types des contractions et leurs applications dans la théorie du point fixe - ABID, Sara; GADI, Samiha; HARIZ BELGACEM, Soumai (university of eloued جامعة الوادي, 2014)
قمنا في ھذا العمل بإعطاء بعض أنواع التقلصات و تطبیقاتھا في نظریة النقطة الثابتة ضمن فضاء متري، حیث كانت ھاتھ الأخیرة وسیلة جد مھمة في حل العدید من المشاكل في مجال:الریاضیات،الفیزیاء، البیولوجیا Meir- نظریة ،Banach وعلم الاقتصاد، أیضا ذكرنا بعض نظریات النقطة الثابتة التي من بینھا نظریة ومن جھة أخرى قدمنا بعض التطبیقات لھا والمتعلقة بحل المعادلات التفاضلیة . Branciari ونظریة Keller والمعادلات التكاملیة .In this work, we gave some types of contractions and their applications in fixed point theory within a metric space, the last one is very important in solving many problems in the field: mathematics, physics, biology and economics, also we mentioned some fixed point theorems by including theorem of Banach ,theorem of Meir-keeler and theorem of Branciari. On the other hand we have provided some of its applications and related solving differential equations and integral equations.
mémoire licence matimatuque
Keywords: الفضاء المتري- المسافة - التقلص – متتالیة كوشي – تطبیق لبشیتزي - الفضاء; Metric space – Contractant – Distance – Lipchitizien mapping – complet space